COVID-19 PATIENTS’ CHARACTERISTIC IN COVID-19 REFERRAL HOSPITAL, SURABAYA, INDONESIA - Titiek Ernawati; Nunung Nugroho; Bernadette Dian Novita; Paul L Tahalele; Niluh Suwasanti; Epriyanto T Darmadi; Kevin Anggakusuma Hendrawan; Albert Setiawan; Audrey Fedora Irawan; Alyssa Claudia Valerie Gunawan; Claudia Tjipto; Kevin Samsudin; Ferdinand Erwin; Gerardo Axel Ruslie; Nevan Go; Melvin F Gonga (Jurnal Berkala Epidemiologi, 2022)
Background: Coronavirus 2019 (COVID-19) is a global pandemic with various clinical manifestations and is affected by multifactor. Epidemiological data of COVID-19 in Indonesia, especially in Surabaya have not been well established yet. Purpose: This study aims to provide the COVID-19 patients profile in Surabaya City, Indonesia. Method: The study data were retrospectively collected from electrical medical records in Primasatya Husada Citra (PHC) Hospital of Surabaya, one of the referral hospitals for COVID-19 in Surabaya. Descriptive and Spearman correlation statistics were done for data analysis. Results: Between 1 July – 31 August 2020, 456 subjects were diagnosed positive for COVID-19 by real-time polymerase chain reaction and enrolled in the study. Study subjects were dominated by the group age of 21-30 (26.75%), male (60.30%), living in East Surabaya (16.22%), and mild to moderate disease severity (47.59%) according to the patient’s clinical manifestation, respiration rate, and peripheral oxygen saturation. Subjects with symptoms were majorly having cough (37.93%), fever (29.38%), malaise (28.07%), and dyspnoea (25.00%). Positive correlation was found between disease severity and group of age (r=0.35; p=0.01), gender (r = 0.13; p=0.01), comorbidities (diabetes mellitus, hypertension, and cardiovascular disease), and X-ray findings (r=0.14; p=0.02). A negative correlation was found between disease severity and the region of domicile (r=-0.15; p=0.01). Conclusion: This epidemiological data of COVID-19 patients in Surabaya city, Indonesia, may help in diagnosing COVID-19 patients and improving health management strategies during a pandemic. Patients need to be aware of COVID-19 and understand disease transmission, especially with symptoms and risk factors.